FOREST HARVESTING: HOW MACHINE TRAFFIC CAN AFFECT SOIL COMPACTION VARIABILITY - Nunes, Ítalo Lima; Minette, Luciano José; Said Schettini, Bruno Leão; Silva, Arthur Araújo; Villanova, Paulo Henrique; Duarte Resende, Julia Hussar (Floresta, 2024)
The forestry sector has seen an increase in wood demand in recent years, requiring greater mechanization and sustainability in forestry operations, operational excellence, and productivity of stands. The effect of harvesting machine traffic on the soil alters its physical properties, causing degradation, soil compaction, and reducing the volumes of wood produced by commercial forests. Thus, the objective of the present study was to evaluate the spatial variability of soil physical attributes after harvesting and skidding operations, carried out by a harvester and forwarder respectively, in a commercial eucalyptus plantation. The study was conducted in two areas in the municipalities of Itanagra-BA and Entre Rios-BA. Samples were collected in three layers (0-0.20 m; 0.20–0.40 m; 0.40–0.60 m) and the following items were evaluated: total porosity, bulk density, and soil penetration resistance. Operations performed by the harvester and forwarder altered soil resistance, with a greater effect on sandy loam soils, decreasing their density and porosity. Regarding the number of forwarder passes, the seventh pass generated the peak resistance, altering soil recovery capacity, causing additional compaction. Operational planning, to reduce the effects of compaction in areas most susceptible to physical soil degradation, is essential in the forestry area, especially when moisture values are high, a factor that favors soil compaction and reduces stand productivity.